Role of institutions in public management: developing case studies for divergent policy systems - Singh, Vaishali (Frontiers in Political Science, 2024)
Public policy management has an intractable nature, and the institutional complexity of governance further exacerbates its practice. Transnational learning cutting across countries and policy areas can contribute to this policy knowledge in dealing with multifarious issues in public management. Understanding the institutional mix in public management in various contexts enhances the existing comprehension of how the national pattern of public management works differently in different socio-economic, cultural, and political settings. The present research aims to study the institutional framework in the form of state structure (unitary or federal) and the nature of executive government (majoritarian or consensual) in delineating the influence of institutions on public management processes in divergent policy systems. The paper undertakes four in-depth country case studies and the public management reforms as a response to institutional pressure are examined using the 4M strategy (Pollitt and Bouckaert, 2017)-Maintain (holding on to existing administrative structures and processes), Modernize (keeping service delivery and regulation up to date), Marketize (efficiency and user-responsive public management), and Minimize (reducing state-led regulation). The case studies highlight the differences in the broad direction and energy of implementation that characterize a particular policy style. The results of the study indicate that even though the institutional dimensions are not present in strict polarization, the impact of the institutional mix is evident in the dominant strategies of public management reforms adopted at the national level.